JSE 32:4 Winter 2018 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2018)
I had the opportunity recently to referee a submission to a clinical psychology journal that examined the apparent manifestation of ESP in the psychiatric setting. I’d been solicited for this chore, not simply because of my background in parapsychology, but also because of my earlier research into dissociative identity (multiple personality) disorder (e.g., Braude, 1995, 1996, 1998). The submitted paper was not awful, and commendably the author had apparently done a considerable amount of reading of relevant works in parapsychology. Nevertheless, the paper had one glaring flaw, and that flaw reminded me of one of my long-standing concerns about the current state of parapsychological research. Moreover, it wouldn’t surprise me if similar concerns can be raised in other areas of frontier science. Although this paper had a reasonably extensive (and perhaps superficially impressive) bibliography, there was not a single mention of important work on the topic done in the mid twentieth-century—most notably, the work of Jule Eisenbud (e.g., Eisenbud, 1946, 1970, 1992) and Jan Ehenwald (e.g., Ehrenwald, 1948, 1978). I found it astonishing that the author would presume to summarize the conceptual and empirical antecedents to the research described in the paper without reference to this material.